IMPLEMENTASI PRINSIP EKONOMI ISLAM DALAM PERILAKU PEDAGANG KULINER DI PASAR KULINER KOTA PADANG PANJANG - Evina Aura Exa Putri; Yefri Joni; Ali Rahman; Rahmi (LPPM STAI Muhammadiyah Probolinggo, 2025)
Many culinary traders in Padang Panjang Culinary Market pay little attention to blessings in their production, provide inadequate service to consumers, and lack understanding of the importance of halal certification. The main problem in this study is how the implementation of Islamic economic principles in the behavior of culinary traders in Padang Panjang Culinary Market. This study aims to analyze the implementation of Islamic economic principles in the behavior of culinary traders in the food and beverage sector in Padang Panjang City, especially in the culinary market. This study uses a descriptive qualitative approach that produces descriptive data and utilizes a theoretical basis so that the focus of the research is in accordance with field facts with data collection techniques through interviews, observations, and documentation. The results of the study indicate that most culinary traders have not fully implemented Islamic economic principles such as monotheism, justice, honesty, responsibility, prophecy, halal and thayyib, and anti-riba in their business activities.